Investigation on the formability and deformation mechanism of Zircaloy-4 sheets with different initial textures during stamping - Deng Siying; Xie Wenlong; Chen Shuaifeng; Song Hongwu; Zhang Shihong (MATEC Web of Conferences)
Zircaloy-4 (Zr-4) sheets used in fuel assembly structural parts are subjected to high temperatures, stresses, corrosive environments, and radiation. Due to the poor formability of Zr-4, cracks usually occur during the fabrication of spacer grids at room temperature. In this research, annealed Zr-4 sheets with two distinct initial textures were studied during stamping. Experimental results showed that the sheet with higher normal Kearns factors exhibited weaker formability, leading to cracking at the punch radius under the same punching depth. Electron backscatter diffraction (EBSD) observations revealed discrepancies in texture evolution under different strain paths during plastic deformation. A multi-scale simulation was conducted to elucidate the deformation mechanisms. Modeling accuracy was validated by comparing crack locations, thickness distributions, and post-deformation textures with experimental results. The contribution of slip and twinning to crack formation was quantified. The simulation indicated that Zr-4 sheets with weaker textures exhibited better deformation compatibility, primarily due to enhanced activation of prismatic slip, whereas sheets with stronger textures showed dominant basal slip activity, which promoted cracking.